Effect of surface treatment on the repair strength of a 3D printed denture base material - Gibreel, Mona; Garoushi, Sufyan; Perea-Lowery, Leila; Atout, Abeer Mohamed; Lassila, Lippo; Vallittu, Pekka K. (Elsevier, 2026)
Statement of problem
The increasing adoption of 3-dimensional (3D) printing in prosthetic dentistry necessitates a comprehensive understanding of how different surface treatments influence the repair strength of 3D printed denture base materials to enhance clinical outcomes. While 3D printing offers significant advantages in fabrication efficiency and customization, concerns persist regarding the mechanical properties and durability of 3D printed materials. Despite its clinical significance, only limited information regarding the repair strength of 3D printed denture bases is available in the literature.
Purpose
The purpose of this in vitro study was to evaluate the effect of different surface treatments on the flexural strength of a repaired 3D printed denture base material.
Material and methods
Bar-shaped specimens (65×10×3.2 mm) of a 3D printed denture base material (V-Print dentbase) were printed, postpolymerized, and submitted to Fourier transform infrared (FTIR) spectrometry to determine the degree of CC conversion (DC%). Eighty-one specimens were assigned to 9 test groups. Sectioned specimens with a 4-mm gap were allocated equally based on the repair surface treatment to the following groups: no treatment (NT), monomer (MN), multiprimer (G-MP), triethylene glycol dimethacrylate (TEGDMA), airborne-particle abrasion (APA), 180-grit paper roughening (180 G), 180 G plus silane (180 G+CB), and bonding agent (SB). Specimens were repaired with an autopolymerizing resin and stored in water for 30 days before testing with a 3-point bend test. Flexural strength data (MPa) were analyzed using the Shapiro-Wilk test (α=.05). Failure modes were classified, and surface-treated specimens were examined using scanning electron microscopy (SEM).
Results
The investigated V-Print dentbase material displayed a high DC (89%). The flexural strength of the intact group was significantly higher than that of all repaired groups (P<.05). The 180 G+CB group achieved the highest repair flexural strength, significantly surpassing that of the NT group (P=.008).
Conclusions
Using 180-grit paper combined with silane significantly improved the repair flexural strength of the investigated 3D printed denture base material, while other treatments showed no significant improvement.